2021
DOI: 10.1158/1538-7445.am2021-42
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 42: Treatment-induced embryonic diapause-like adaptation through suppression of Myc activity as mediator of drug persistence in cancer

Abstract: Chemo-persistent residual tumors are a major barrier for curative cancer therapy and provide a reservoir of cancer cells for eventual relapse. This clinically critical tumor cell population is poorly understood and lacks faithful in vitro models. We compared the transcriptional profiles of paired samples from patient with solid tumors or hematological neoplasias at the stage of post-treatment residual tumors or minimal residual disease vs. at their respective baselines. For a large proportion of patients, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on transcriptomics, different mechanisms have been proposed over time to explain tumor or leukemia cell persistence after drug treatment because of microenvironmental protection. Features identified in leukemia cells remaining after chemotherapy include dormancy and a diapause-like state (14,84,85). Based on numerous studies, it seems clear that indeed increased quiescence is a common feature of MRD cells in BCP-ALL as well: Turati et al ( 86), Ebinger et al (14) and our own studies all showed that MRD/DTP cells have reduced activity of MYC and E2F pathways.…”
Section: Common Features Of Dtp Bcp-allmentioning
confidence: 69%
“…Based on transcriptomics, different mechanisms have been proposed over time to explain tumor or leukemia cell persistence after drug treatment because of microenvironmental protection. Features identified in leukemia cells remaining after chemotherapy include dormancy and a diapause-like state (14,84,85). Based on numerous studies, it seems clear that indeed increased quiescence is a common feature of MRD cells in BCP-ALL as well: Turati et al ( 86), Ebinger et al (14) and our own studies all showed that MRD/DTP cells have reduced activity of MYC and E2F pathways.…”
Section: Common Features Of Dtp Bcp-allmentioning
confidence: 69%
“…Although many studies have been focused on the genetic mechanisms of drug resistance, emerging evidence suggests the importance of residual drug-tolerant persister (DTP) cancer cells, which survive the initial targeted therapy via diverse, reversible and non-mutational mechanisms, such as transcriptional, epigenetic, and metabolic reprogramming (16)(17)(18)(19)(20)(21)(22)(23). Recent studies have demonstrated an embryonic diapause-like adaption enabling the cancer treatment persistence (24,25). DTP cells, which underlie the phenomenon known as minimal residual disease (MRD), constitute a reservoir of slow-cycling cells that can drive irreversible acquired drug resistance upon long term drug treatment, which eventually leads to the cancer relapse (9)(10)(11)26).…”
Section: Introductionmentioning
confidence: 99%